Exploring bacterial flora in oral squamous cell carcinoma: a microbiological study. (February 2014) - Metgud, R; Gupta, K; Gupta, J
Abstract The oral cavity contains a unique and diverse microﬂora. While most of these organisms exhibit commensalism, shifts in bacterial community dynamics cause pathological changes within the oral cavity and at distant sites. We assessed the microbial flora using cultured saliva and oral swabs from subjects with oral squamous cell carcinoma (OSCC) and healthy controls. Microbial samples were collected from the carcinoma site, contralateral healthy mucosa, and saliva of the study group and samples were collected from healthy mucosa and saliva of controls. Samples were stored on ice and transported to the laboratory for culture. The median number of colony forming units (CFU)/ml at carcinoma sites was significantly greater than at the contralateral healthy mucosa. Similarly, in saliva of carcinoma subjects, the median number of CFU/ml was significantly greater than in saliva of control subjects.